Problem-Based School Principal Competency Improvement Training: Pelatihan Peningkatan Kompetensi Kepala Sekolah Berbasis Masalah - Kristiawan*, Nana; Ramadhan, Putri Utami; Huda, Muhammad Nurul; Chahyati, Siti; Ramadhina, Zahra (Universitas Lancang Kuning, 2025)
The Problem-Based Principal Training activity aims to improve the competence of principals. This training is a solution to the minimal qualifications of prospective principals in the Mitra Grogol Petamburan environment by involving 25 participants. The training method consists of preparation, implementation, evaluation and reflection and follow-up. The results of the training evaluation showed an increase in the understanding of participants in the